Strategi Guru Pendidikan Agama Islam dalam Menghadapi Dominasi Informasi Keagamaan Digital: Analisis Literatur terhadap Literasi Digital dan Pembelajaran PAI - Mike Andrini; Agus Pahrudin; Achi Rinaldi; Ali Murtadho (Universitas Muhammadiyah Magelang, 2026)
The development of digital technology has significantly transformed the learning ecosystem of Islamic Religious Education (IRE), particularly in terms of access to and distribution of religious information among students. This study aims to analyze and synthesize various research findings related to Islamic Religious Education teachers strategies in responding to the dominance of digital religious information, focusing on digital literacy, pedagogical strategies, and the use of digital media in learning. This research employs a qualitative approach using a library research method and content analysis techniques. Data were collected from various scientific journal articles, books, and academic publications published within the last ten years. The findings indicate that the dominance of digital religious information has led to a shift in knowledge authority, variations in students understanding, and potential misconceptions in interpreting religious teachings. In response, Islamic Religious Education teachers implement strategies such as strengthening digital literacy, applying pedagogical approaches including critical discussion and clarification, and utilizing digital media as a learning tool and value reinforcement medium. The synthesis reveals that these three aspects are interconnected and need to be integrated into a comprehensive learning framework. This study emphasizes that Islamic Religious Education teachers play a crucial role as facilitators, mediators, and guides in developing critical, contextual, and value-based religious understanding in the digital era.